Science Education Scholars’ Views and Approaches to Qualitative Research - Prince, Adepeju (Journal of Educational Technology and Instruction, 2023)
The guidelines for qualitative research have been established in previous studies. However, it is subjected to the interpretation of individual researchers due to its nature in explaining complex phenomena about human interactions. Many areas of social science research utilize qualitative research as a primary research method or in addition to quantitative research. However, the approach of science education scholars has minimal documentation. This qualitative study uses a phenomenological approach to explore the views of four science education scholars and their approach to how they use qualitative research in their published works. The finding revealed that science educators ventured into qualitative research due to the influence of professors and courses they took in graduate school. Additionally, they established the strength of qualitative data in explaining the numbers.